Indecisiveness moderates the relationship between rumination modes and depressive symptoms - Winchell, Brandon; Ezawa, Iony D. (Frontiers in Psychology, 2025)
IntroductionMajor depressive disorder is a debilitating and common mental health condition. Rumination and indecisiveness are both well-established cognitive risk factors for depressive symptoms, but their interactive effects remain underexplored. Drawing on theories about rumination's level of construal, which distinguish between abstract and concrete modes of thinking, this study examined whether aversive indecisiveness moderates the relationships between rumination modes (abstract and concrete) and concurrent depressive symptoms.MethodWe recruited two samples: an undergraduate student sample (Sample 1, N = 412) and a general population sample (Sample 2, N = 258). Participants completed self-report measures of depressive symptoms, rumination modes, and indecisiveness. Robust linear regression was used to test moderating effect of aversive indecisiveness on rumination modes while controlling for gender, age, income, and timepoint.ResultsAversive indecisiveness significantly moderated the relationship between abstract rumination and depressive symptoms in both samples, such that the positive association was stronger at higher levels of indecisiveness. In Sample 2, aversive indecisiveness also moderated the relationship between concrete rumination and depressive symptoms, such that the negative association was stronger at higher levels of indecisiveness.DiscussionThese results suggest that the co-occurrence of abstract rumination and aversive indecisiveness may confer heightened risk for depressive symptoms, highlighting the importance of considering both factors jointly in understanding and treating depression.